Enhancing financial transparency: The impact of siskeudes application in Kediri Regency - Mutiara, Nisa (Center for Economics, Business and Entrepreneurship Development Faculty of Economics and Business, Universitas Muhammadiyah Malang, 2024)
The Village Law (Law Number 6 of 2014) mandates local governments to manage village affairs and funds, leading to the establishment of the Village Fund. This study examines how implementing the Village Financial System (SISKEUDES) application affects transparency and, consequently, the quality of financial reports in Kediri Regency. Using quantitative research with 185 samples from 343 villages, the study finds that SISKEUDES directly improves financial report quality and indirectly through transparency mediation.